Dukungan keluarga dan jadwal makan dan sebelum edukasi berhubungan dengan kepatuhan jadwal makan pasien diabetes melitus (DM) tipe 2 rawat jalan yang mendapat konseling gizi di RSUD Kota Yogyakarta - Martalena Br Purba; Endah Sri Rahayu; Hemi Sinorita (Minat S2 Gizi dan Kesehatan, Prodi S2 IKM, FK-KMK UGM, 2010)
Background: Diabetes mellitus (DM) is a clinical syndrome with symptoms of hyperglycemia, urinary glucose excretion and disorder of insulin mechanism. Approximately 90-95% of diabetic patients suffer from type 2 DM. Various studies show that compliance to treatment of chronic disease in general is low. Compliance to eating or food frequency amongst DM patients in hospital in particular is very low. The success of self management of blood glucose (SMBG) needs participation of the patient, families, and educator team.Objective: To study the factors affecting eating compliance particularly eating schedule among type 2 diabetic out-patient who had nutrition counseling in RSUD Kota Yogyakarta.Method: It was an observasional study with cross sectional design and purposive sampling. Data collection was done in October 2008 with 98 subjects. The sampel were type 2 diabetic out-patients according to inclusion criteria at out- patient clinic in RSUD Kota Yogyakarta. Statistical test with 95% confidence interval was applied to investigate factors infuenced eating compliance.Results: There were no correlations between eating compliance and disease duration (RP= 1,253 and p =0,403), and also with type of occupation (RP= 1,047 dan p= 1,000). However, it was found that family support affected eating compliance (RP= 1,723 dan p= 0,025) as well as eating schedule before nutrition counseling (RP = 2,151 and p= 0,02).Conclusion: Duration of disease and type of occupation did not affect eating compliance. Nevertheless, family support and eating schedule before nutrition education affected eating compliance among type 2 DM out-patients in RSUD Kota Yogyakarta.